Modernist goods : primitivism, the market and the gift - Willmott, Glenn, 1963- (Book collections on Project MUSE., 2008)
The politicised interpretation of literature has relied on models of economic and social structures that oscillate between idealized subversion and market fatalism. Current anthropological discussions of mixed gift and commodity economies and the segmented politics of house societies offer solutions to this problem and suggest invaluable new directions for literary studies. Modernist Goods uses recent discussions of gift and house practices to counter an influential revisionist trend in modernist studies, a trend that sees the capitalist marketplace and its public sphere as the uniquely determining institutional structures in modern arts and culture.Glenn Willmott argues that a political unconscious forged by the widespread marginalisation of pre-capitalist institutions comes to the fore in modernist primitivism. Such primitivism, he insists, is not superficially exoticist or simply appropriative of the cultural heritage of others. Rather, it is at once parodic and authentic, and often, in the language of Julia Kristeva, abject. Modernist Goods examines such writers as Yeats, Conrad, Eliot, Woolf, Beckett, H.D., and Joyce to uncover what the author views as their displaced aboriginality and to investigate the relationship between literary modernism and aboriginal modernity. By bringing current anthropological developments to literary studies, it aims to rethink the economic commitments of modernist literature and their political significance.